Antarala of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The antarala (vestibule) of the Hazareshwar Temple is shallow and minimalistic, with no decoration except for the floor. Here, a moonstone serves as a stepping stone, leading to the threshold of the garbhagriha (sanctum sanctorum).